The Womanhood of Roko Molas Poco Rite in Manggarai's Patriarchal Culture: A Discourse on Simone de Beauvoir - Letsoin, Yetva Softiming; Sembiring, Kristinus; Suhartini, Yosefina Elsiana (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
This paper focuses on exploring the role of women in the Roko Molas Poco rite in Manggarai. This study applies a discourse approach by referring to Simone de Beauvoir's concept of feminism. She views women as